(untitled) - Colson, Charles W. 1931-; Eckerd, Jack, 1913- (Dallas, TX Word, 1991)
Includes bibliographical references and index.
Keywords: Quality of products -- United States; United States -- economic conditions -- 1981-; Work ethic -- United States